Pengaruh Jaw Relaxation terhadap Tingkat Nyeri - Maria Diah Ciptaning (Poltekkes Kemenkes Malang, 2018)
Caesarean Section is a surgical procedure in which a fetus is delivered from the uterus through an abdominal wall incision. The most domminant issue after having a caesaran section is pain. Pain can be resolved either pharmacologically or nonpharmacologicallly. Jaw relaxation technique is one of the non-pharmacological methods to reduce pain by combining jaw muscle relaxation and breathing relaxation to improve coping mechanisms and to release endorphins. The purpose of this study was to compare the pain levels after having a caesarean section, before and after doing jaw relaxation. The design of this study was pre-experimental research with one group pretest and postest design. It used purposive sampling technique with 12 respondents as its sample. The result indicated that 100% of respondents experienced pain before having Jaw Relaxation. 83.3% of respondents felt that their pain has decreased after having Jaw Relaxation. To analyze the data, it used Wilcoxon Signed Rank test, and it got p-value 0.002 as the result. The conclusion of this research is Jaw Relaxation has a significant effect on the levels of post-operative pain ofthis caesarean section. Jaw Relaxation could be used as a nurse intervention by making its standard of operational procedure to solve the pain problem.